Współczesne nurty badań nad dzieckiem i dzieciństwem. Przegląd perspektyw - Kiszka, Monika (Studia Edukacyjne, 2025)
The article contains considerations on contemporary research on children and childhood, presenting various approaches, concepts, and research paradigms. Research on children and childhood is conducted on the basis of many theoretical and methodological paradigms. Childhood and child development research is based on diverse theoretical and methodological frameworks. For the contemporary identity of research, the trends of childhood studies and childism discussed in the article are particularly important. The contemporary identity of research is significantly shaped by trends in childhood studies and childism, which are explored in the article. Childhood is undoubtedly one of the major stages in a person’s life, serving as the foundation for every subsequent stage. Therefore, scientific reflection on the development of research trends and paradigms in this topic is extremely important. It is crucial to conduct scholarly analysis on the evolution of research trends and paradigms in this area.